(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
The purpose of this research is to learn about the different types and reasons why people use code mixing in their daily conversations in Poleang-Bombana, South East Sulawesi. There are two kinds of data sources in this research, namely primary data and secondary data. The writer used direct observation and asked some questions that had been prepared by the researcher before. This study used descriptive qualitative research with an analytical approach. In Poleang, Bombana, data were gathered through observations and interviews. The writer found that there were three types of code mixing, namely insertion, alternation, and congruent lexicalization.